Hyperbolic stefan problem in a curvilinear sector - Berehova, H. I.; Kirilich, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
The problem with unknown boundaries for a first-order semilinear hyperbolic system is studied in the case where the curve of definition of the initial conditions degenerates to a point. An existence and uniqueness theorem for a classical solution of the problem is proved for small t.